Brain Imaging Exploration of the Representational Structures Supporting Observation of Abnormal Finger Postures. - Granja Espirito Santo, Miguel (2018)
Observing body related abnormalities such as broken limbs (like fingers) can lead to a vicarious somatosensory experience. Such responses depend on a complex interaction between different brain regions in order to give rise to a somatosensory experience based on visual stimulation alone. In this thesis, I use multiple imaging techniques to demonstrate this is an example of embodied simulation, an ingrained ability of the brain that allows an observer to simulate others’ experiences based on somatosensory and lateral occipital involvement.